Salmon drying on racks in Anvik, Alaska, 1913 - Curtis, Asahel, 1874-1941
Salmon drying on racks in Anvik Alaska, 1913. Caption on image: Curtis. Seattle, Wash. 29219. On verso of image: Drying salmon on the lower Yukon. The coming of the salmon is the harvest time of the Indians of the Yukon. Salmon furnishes food for them and their dogs. Without dried salmon they could not maintain their dog teams and without dog teams winter travel would be impossible. Anvik, 1913.